Thyroid Function/Antibodies in Sudanese Patients with Preeclampsia - Elhaj, Enaam T.; Adam, Ishag; Alim, Ammar; Elhassan, Elhassan M.; Lutfi, Mohamed F. (Frontiers in Endocrinology, 2015)
Preeclampsia is an important cause of maternal and prenatal morbidity and mortality in the developing countries. Changes in thyroid function/antibodies profiles in preeclamptic women are controversial and were never investigated before in Sudan. A case-control study was conducted at Medani Hospital, Sudan to investigate thyroid function/antibodies in preeclampsia. The socio-demographic, medical history was gathered using questionnaire. Thyroid hormones (TSH, free T3, T4) anti-TPO and anti-TG antibodies) were measured using ELISA. The three groups [controls (55) and mild (68) and severe preeclampsia (55)] were matched in the age and parity. While median (interquartile range) of TSH was significantly lower, the free level of both T3 and T4 were significantly higher in women with preeclampsia than in the healthy controls. There was no significant difference in the TSH levels in women with mild and severe preeclampsia. In comparison with women with mild preeclampsia, women with severe preeclampsia had significantly higher levels of free T3 and significantly lower levels of free T4. While anti -TPO antibodies were significantly higher, anti-TG antibodies were significantly lower in women with preeclampsia. Likewise anti -TPO antibodies were significantly higher and anti-TG antibodies were significantly lower in women with severe preeclampsia than in women with mild preeclampsia. In linear regression, preeclampsia was significantly associated with TSH (−0.675 IU//ml, P = 0.009), free T3 (0.977 pg/ml, P < 0.001) free T4 (0.186 ng/dl, P < 0.001) levels. In contrast to anti-TG antibodies and TSH, Sudanese patient with preeclampsia had higher levels of T3, T4, and anti-TPO antibodies irrespective of parity, gestational age, and hemoglobin levels.